Evaluation of Tritrichomonas foetus infection clearance in heifers immunized with a single intravaginal dose of formaldehyde fixed strain B1 cells - Martinez, Florencia Gracia; Fuchs, Lumila Ivana; Ramirez, Rosana; Breccia, Javier Dario; Oyhenart, Jorge (Elsevier, 2018)
Vaccines against Tritrichomonas foetus have been shown to reduce the time of infection after natural or experimental exposure. The object of this study was to assess the protection against T. foetus infection conferred by a single vaginal instillation of formaldehyde fixed T. foetus cells. Aberdeen Angus virgin heifers were randomly allocated to 3 groups of 12 individuals to receive placebo or formaldehyde fixed T. foetus cells prepared following one of two procedures (formalin or freshly prepared solution) and six weeks later they were challenged with 106T. foetus trophozoites. The median time for clearance among control heifers was 93.75 days while in animals immunized with formaldehyde fixed T. foetus it was 45 days. A single vaginal dose of cells fixed with fresh formaldehyde solution gave a rate of decay of infection per unit of time of 2.54 (CI 95% = 1.07;6.01).